Efeito da laserterapia de baixa intensidade no controle da dor, edema e trismo pós cirurgias de terceiros molares inferiores - Prado, Lucianna de Freitas (2017)
The use of laser therapy in dentistry for repair of oral tissues is an important auxiliary agent in third molar surgeries, modulating the effects of inflammation and alleviating postoperative symptoms, promoting the reduction of edema and pain, allowing better tissue repair involved. The purpose of this study was to test two protocols of low-intensity laser therapy to evaluate pain control, edema and trismus in the postoperative period of lower third molar surgeries. It is a randomized, double-blind, crossover clinical study. A total of 42 procedures were performed in 21 patients, with the following protocols: "A" protocol: laser application immediately after the surgical procedure, 24 and 48 hours after surgery. Protocol "B": laser application immediately after the surgical procedure and placebo after 24 and 48 hours. The modulation of the apparatus followed the following technical parameters: 660nm, dose of 5 J / cm2, t 10 s, P 20 mW, for applications in 4 intraoral points, and 789 nm, dose of 30 J / cm2, t 20 s / point, P 60 mW, for the application of 8 extraoronal points. The evaluations of the pain, trismus and edema were performed by a blind evaluator, in the following times: immediate postoperative, 24, 48 hours and 7 days after surgery. EVA was used to evaluate the pain, and no statistical differences were observed in the results, although the number of rescue analgesic medication was lower when applied to the "A" protocol. In the assessment of edema, there was no statistically significant difference in any of the protocols used. In the evaluation of trismus, only the evaluation done in the 48-hour PO, obtained a better result for the "A" protocol. It can be concluded that the low intensity laser therapy by the "A" protocol presented better results in the control of trismus and pain, and did not have significant differences for edema between the protocols used